Abstinence and alcohol consumption among secondary school students - Bonito, Jorge (2014)
A young person tend to drink alcohol due to the curiosity, imitation belonging to a peer group and in some cases the motivation of the family. Alcohol is therefore socially tolerated moderate alcohol consumption can lead risk forms of consumption. The study shows that attempts to understand the consumption and abstinence from alcohol consumption among young people in secondary education who attend a school in the district of Evora in co use of learning spaces and leisure. The research was qualitative in nature developed using the direct method of data collection. Ten interviews were held, five to five to young consumers and non-consumers, the students of the 10th and 12th grades. The results point towards the first contact with alcoholic beverages held in nocturnal atmosphere by active or tacit influence of peers. The alcoholic behavior is common and inherent in party environments. A behavior modification, group membership, seems to indicate the change of individual behavior in relation to alcohol consumption. Young people are not consumers have tried drinking alcohol however, want the taste of some, or the effects they cause, are not stimulating consumption, unnecessary considering your intake to personal recovery and for peer interaction.